Cover Image, Volume 234, Number 9, September 2019. Issue 9 (24th May 2019) - Hertig, Vanessa; Matos‐Nieves, Adrianna; Garg, Vidu; Villeneuve, Louis; Mamarbachi, Maya; Caland, Laurie; Calderone, Angelino
Abstract : Cover : The cover image is based on the Original Research Article Transcriptional cofactor Vgll2 is required for functional adaptations of skeletal muscle induced by chronic overload by Masahiko Honda et al., DOI: 10.1002/jcp.28239 .